2003
DOI: 10.1086/378644
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Persistence of the Plant‐Mycorrhizal Mutualism: A Hypothesis from Species Coexistence Theory

Abstract: In diverse mutualisms, it is common for potential partners to vary in the quality of benefits they provide. When weakly beneficial mutualists and parasites have a competitive advantage over strongly beneficial mutualists, it is not clear how strongly beneficial mutualists persist. If mutualism is destabilized by competitive superiority of weakly beneficial mutualists or cheaters, then mechanisms providing for stable coexistence among competing species may also provide for the persistence of mutualism. We analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 49 publications
1
79
2
Order By: Relevance
“…For example, in the yucca-moth mutualism, yucca flowers heavily damaged by the oviposition of some species of pollinating yucca moth tend to be aborted (Pellmyr & Huth 1994), which selects for lower levels of oviposition (and thus, higher seed production). Similarly, in the legume-rhizobia mutualism, Kiers et al (2003) have demonstrated experimentally that soybean plants selectively reduce oxygen permeability in root nodules containing non-nitrogen fixing rhizobial bacteria, reducing their fitness (West et al 2002b, see also Hoeksema & Kummel 2003 on mycorrhizae).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the yucca-moth mutualism, yucca flowers heavily damaged by the oviposition of some species of pollinating yucca moth tend to be aborted (Pellmyr & Huth 1994), which selects for lower levels of oviposition (and thus, higher seed production). Similarly, in the legume-rhizobia mutualism, Kiers et al (2003) have demonstrated experimentally that soybean plants selectively reduce oxygen permeability in root nodules containing non-nitrogen fixing rhizobial bacteria, reducing their fitness (West et al 2002b, see also Hoeksema & Kummel 2003 on mycorrhizae).…”
Section: Introductionmentioning
confidence: 99%
“…One approach that is proving promising is the concept of host coercion (Murray 1985;Herre 1989;West & Herre 1994;Yu 2001;Ferdy et al 2002;West et al 2002a,b;Hoeksema & Kummel 2003;Yu & Ridley 2003;Yu et al 2004a;Edwards et al in preparation), which argues that the partner controlling the physical resources (the host) ultimately controls the relationship, as opposed to the partner providing the services (the visitor).…”
Section: Introductionmentioning
confidence: 99%
“…The reason could be the ECM functional diversity. Plants can control ECM colonization by regulating C allocation to short or fine roots (diameter < 2 mm), according to the intensive relationship between the symbionts and host plants (Hoeksema and Kummel 2003). Thus, specific fungi with low carbohydrate requirements are often favored as symbionts in forest ecosystems.…”
Section: Ectomycorrhizal Symbiosis Under Elevated Co 2 and Omentioning
confidence: 99%
“…They are ubiquitous in nature and often essential for the functioning of ecosystems (Smith and Donoghue, 2008;Yoder et al, 2010). In addition to the ecological benefits of mutualistic interactions for species co-existence and biodiversity (Hoeksema and Kummel, 2003), the apparition of mutualistic interactions has been documented to trigger the diversification of organisms in several clades (Harry et al, 1996;Pellmyr and Krenn, 2002;Litsios et al, 2012). As a consequence, many ecosystems are currently dominated by species involved in one or several mutualistic interactions (Lewinsohn et al, 2006).…”
Section: Introductionmentioning
confidence: 99%